Interannual variation of springtime biomass burning in Indochina: Regional differences, associated atmospheric dynamical changes, and downwind impacts - Huang, Wan‐Ru; Wang, Sheng‐Hsiang; Yen, Ming‐Cheng; Lin, Neng‐Huei; Promchote, Parichart (Journal of geophysical research. Atmospheres, 2016)
During March and April, widespread burning occurs across farmlands in Indochina in preparation for planting at the monsoon onset. The resultant aerosols impact the air quality downwind. In this study, we investigate the climatic aspect of the interannual variation of springtime biomass burning in Indochina and its correlation with air quality at Mt. Lulin in Taiwan using long‐term (2005–2015) satellite and global reanalysis data. Based on empirical orthogonal function (EOF) analysis, we find that the biomass burning activities vary with two geographical regions: northern Indochina (the primary EOF mode) and southern Indochina (the secondary EOF mode). We determine that the variation of biomass burning over northern Indochina is significantly related with the change in aerosol concentrations at Mt. Lulin. This occurs following the change in the so‐called India‐Burma Trough in the lower and middle troposphere. When the India‐Burma Trough is intensified, a stronger northwesterly wind (to the west of the trough) transports the dryer air from higher latitude into northern Indochina, and this promotes local biomass burning activities. The increase in upward motion to the east of the intensified India‐Burma Trough lifts the aerosols, which are transported toward Taiwan by the increased low‐level westerly jet. Further diagnoses revealed the connection between the India‐Burma Trough and the South Asian jet's wave train pattern as well as the previous winter's El Niño–Southern Oscillation phase. This information highlights the role of the India‐Burma Trough in modulating northern Indochina biomass burning and possibly predicting aerosol transport to East Asia on the interannual time scale. Key Points The springtime biomass burning activities in Indochina vary with two geographical regions: northern Indochina and southern Indochina The interannual variation of biomass burning over northern Indochina is closely related with the changes of PM10 at Mt. Lulin in Taiwan The changes of the India‐Burma Trough are important to the modulation of the aerosol transport pattern from northern Indochina to Taiwan